The Emotional Impact of Evil: Philosophical Reflections on Existential Problems - Colgrove, Nicholas (Open theology, 2019)
In The Brothers Karamazov , Dostoyevsky illustrates that encounters with evil do not solely impact agents’ beliefs about God (or God’s existence). Evil impacts people on an emotional level as well. Authors like Hasker and van Inwagen sometimes identify the emotional impact of evil with the "existential" problem of evil. For better or worse, the existential version of the problem is often set aside in contemporary philosophical discussions. In this essay, I rely on Robert Roberts’ account of emotions as "concern-based construals" to show that theistic philosophers can effectively address the existential problem (and so, the problem should not be set aside). In fact, addressing the emotional impact of evil is crucial, I argue, given that resolving just the impact of evil on agents’ beliefs about God constitutes an incomplete response to the problem of evil.